Fiber Optic Data Communication: Technological Trends and Advances - Decusatis (Casimer) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2007)
Optical Fiber Communications
22.5
Keywords: Optical Fiber Communications